Mental health programming for law enforcement: a first look at trends and perceptions of effectiveness - Bonner, Heidi S. (Journal of crime and justice, 2022)
Traumatic events, irregular shifts, and other job-related stressors impact the mental health of law enforcement officers. However, little information exists regarding the availability and perceptions of the effectiveness of mental wellness programming and resources in police departments and sheriff’s offices across the United States. Using a paper and pencil survey with a stratified random sample, we explored the types of mental wellness programming available throughout agencies in the United States and the perceived effectiveness of such programs. Most respondents provided information on mental wellness resources, employee assistance programs, and external event response. Resiliency building/training and annual mental wellness checks were the least common program/resource currently provided. Peer counseling/support was slightly more common in police departments, while external event response, chaplain support, and mentoring programs were more common in sheriff’s offices. Respondents generally perceived chaplain support, psychological services, external event response, and resiliency building/training to be effective forms of mental wellness programming, while annual mental wellness checks, mental wellness resources, and mentoring programs were deemed less effective. Limitations and directions for future research are provided.